Manila Doctors Hospital clinic expansion in Lancaster New City, Cavite - a demand feasibility study - Jao, Bernard H.
Manial Doctors Hospital (MDH), under the guidance of Metrbank Foundation, Inc., has continued to grow and now looking at venues for satellite clinic expansion. PROFriends has asked MDH to look at Lancaster New City Cavite (LNCC) as a possible site for this expansion. This descriptive study was designed to look at the demand feasibility for a clinic in LNCC. With authorization from MDH, the author proceeded to coordinate with PROFriends for the possibility of conduction a survey within the premises of LNCC. A survey questionnaire was developed in both English and Taglish. LNCC is made up of 51 planned phases. To get a sample population, a 2-stage geographic cluster sampling methods was used to select the phases, while systematic sampling (k=2) was used to select the households. A total of 116 households weresurveyed. The households had an average size of 4.18 members and majority of those sampled were below 40 years old. Majority of the households had at least one outpatient consultation from the period of January to September 2016. Among the households , 29.3% consulted more than 5 times during this period. Majority of the consults were for adult checkups 71%, followed by pediatric checkups at 33%. Based on the location of consultation, 47.8% of the households consulted only within Cavite while 32.7% consulted exclusively in Metro Manila. Proximity was the number one reason for patronage of these clinics. Around 91% of those sampled have heard about MDH before, mostly from friends and relatives. If MDH would make a satellite clinic, the residents said they would most likely utilize the laboratory. They would also need dental, internal medicine and pediatric services. Using Fisher Exact test, it was found out that residents living in the higher end areas of Lancaster were more likely to consult within Metro Manila and those with health cards consulted from often.